Ultrasonic-assisted high-speed micro-milling of Ti6Al4V - Mahmat, Aybars; Agar, Salih; Tosun, Nihat (Springer Heidelberg, 2024)
In this study, the effects of different cooling techniques and process parameters on the performance characteristics of ultrasonic and conventional micro-milling (1-micron fixed amplitude, 20 and 30 kHz frequencies) of Ti6Al4V alloy were experimentally investigated. The impact of independent factors on tool life, cutting force, surface topography, surface roughness and cutting temperature was determined in order to find out machinability characteristics in this paper. Machining operations were performed under 20,000, 40,000 and 60,000 rpm revolution speed. The cutting depth and feed rate of the machining were kept fixed at 0.02 mm and 0.66 mm/s, respectively. Uncoated carbide and TiSiN-coated carbide cutting tools were used in machining operations. Dry machining and two different minimum quantity of lubrication (MQL) methods were used as cooling methods. According to the results achieved in the existing study, the ultrasonic micro-milling improved the surface roughness, reduced cutting forces, cutting zone temperature, and cutting tool wear. It was also found that MQL methods among other methods used in the present study have a greater effect on performance characteristics. As the spindle speed increased, the workpiece surface roughness, cutting force and tool life decreased, while the cutting zone temperature increased.
Keywords: Machining; MQL; Ultrasonic; Performance characteristics; Micro-milling